Construction Three Charts Based on Inter Quartile Range and Comparison of Efficiency with Three Charts Based on Range - Dlshad Mahmood Saleh; Dashty Ismil Jamil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study addresses an important application of statistics in the field of industry, which is known as statistical process control. Producing high quality products order to meet consumer fulfillment requirements had always been the main issue of the quality management. In this paper, Construction of three statistical quality control charts based on inter quartile range and compared with three quality control charts based on range to justify the efficiency and sensitively of the new charts for detecting are out of control cases.